Caracterização da suinocultura em Mossoró, Rio Grande do Norte: aspectos sanitários e riscos de zoonoses - Leite, Alexandro Iris [UNESP] (2014)
The study aimed to characterize the pig industry in Mossoró, Rio Grande do Norte, in its health aspects, identifying the risks of zoonoses and specifically know the reality of brucellosis and leptospirosis in the local herd. The research included a quantitative epidemiological study, with descriptive design in which a situational analysis of the top 20 commercial swine farms was conducted through visits and interviews with producers. Also comprised a cross-sectional design in which 412 blood samples from pigs were collected for the detection of antibodies anti-Brucella ssp., through the buffered acidified antigen (TAA) and the complement fixation test (RFC) tests, and detection of antibodies anti-Leptospira spp., by microscopic agglutination test (MAT). The results showed that the swine in Mossoró-RN presented a profile of subsistence, with the use of family labor, and farming system showed serious health problems, several risks have been detected for the occurrence of zoonoses. The prevalence of brucellosis in animals was 27.0% in the AAT test and 17.5% in the RFC; 55% of the surveyed properties had at least one positive animal, and these prevalence ranged from 6.7% to 80.0%; the risk factors that were influencing the occurrence of the disease were the presence of rats in the creations, contact with cattle and the young age of the animals. The prevalence of leptospirosis was 78.6%, with positive samples for 15 serovars, with prevalence of serovars Icterohaemorrhagiae and Pomona; there were reactors in all the worked farms (100%), and the percentage of infection for each farm ranged from 25% to 100%; the risk factors that were associated with leptospirosis were the containment system of animals and bad sanitation of breeding facilities; the use of treated water for watering the animals was a protective factor. These findings revealed that the swine had serious health problems; etiological ...